Rainfall in Azul and its relationship with the phenomenon el Niño Southern Oscillation (ENSO) - Vilatte, Carlos Alberto (2017)
The aim of this paper was to verify whether there is a correlation between rainfall conditions that occurred in Azul, Buenos Aires (Lat 36°45' S; 59°57' W and Long altitude 137 m), between 1950 - 2015, and thermal anomalies generated in ENSO episodes in its warm phases - El Niño (EN) and cold - La Niña (LN), using a monthly series and annual rainfall. The annual rainfall showed a slight positive trend in the case of EN and below the central tendency for LN; however, these differences were not significant at 5% probability. In the monthly scale very low values were found in the Pearson Index, where only for the process LN, and June (IP 0.5692), the linear relationship and t-Student analysis were slightly significant, 5%. Therefore, the existence of a change in the local rainfall regime in the years in which this process was present cannot be confirmed.